POLICY IMPLEMENTATION INCREASED OF REGIONAL ORIGINAL INCOME (Study at Jasa Yasa Regional Company of Malang Regency) - Dwi Hari Cahyono; Slamet Muchsin; Afifuddin Afifuddin (Ji_Mild (Jurnal Ilmiah Magister Ilmu Administrasi), 2020)
ABSTRACTThis research is motivated by the desire to strengthen the regional revenue structure and to make this region capable and independent, so the contribution of the local area collected based on regional regulations in accordance with the laws and regulations is always improved, especially from the Regionally Owned Enterprises (BUMD).Business Entity whose capital is owned by the region, in this case (Regional Services Company of Malang Regency). Is part of a Regionally-Owned Enterprise in the Regency. Malang, which contributes Regional Original Revenue to Malang Regency, but in its journey there are several business units that have not yet made a maximum contribution to Malang Regency's Original Regional Revenue. In-depth observations are described in the case study description. In the Regional Services Company Yasa Malang Regency). How to collect data using two-way communication between interviews with interviewees, and go directly to the field. while in-depth observation through observation, and conducting interviews, while the analysis and interpretation using a reciprocal method from Milles Hubermas & Saldana (2014).The research findings revealed the following results 1). The journey of implementing the decision to increase the potential of local revenue by increasing the quality of human resources, optimizing tourism promotion strategies by opening a kind of secretariat that explains tourism or visitors who use to introduce tourism objects, arrange and implement ways of utilizing wealth to produce optimal results, make improvements or the addition of infrastructure in the Business Unit, efficiency or savings in company expenses / costs. 2). The problems faced in carrying out policies to improve local opinion include: the problem has not been given the compensation management of Songgoriti baths by PT Lembu Nusantara Jaya. The existence of Songgoriti's baths and printing are considered dead, so the existence of these two units has not yet contributed to the maximum Local Revenue. In addition, the factor is less effective and less efficient target of earning revenue. 3). Analysis of the model implementation of the policy to increase local revenue, in its development has not yet been maximized, even though the management system has changed, so that the revenue condition is still below this standard, the Directors of the Regional Service Company of Malang Regency are required to take steps to look for a solution such as formulate plans and implement strategies to utilize assets to gain greater profits/profits, while also finding unique ways to improve work processes so that the Regional Service Company can have a better level of accountability Keywords: Policy Implementation, Increasing Local Revenue, Regional Company Jasa Yasa.